PLANNING OF INCOME AND EXPENDITURES IN HIGHER EDUCATION INSTITUTIONS (E Global Congress, 2025)
Financial planning, that is, scientifically determining income and expenditures, plays a crucial role in the effective organization of higher education institutions' activities. In the current market economy conditions, educational institutions must possess financial independence, correctly allocate their funds, and use them efficiently. This, in turn, requires organizing every financial operation based on a clear plan. Effective planning of income and expenditures ensures the sustainable development of higher education institutions, improves the quality of education, and enables the strengthening of the material and technical base. Therefore, this issue holds not only economic but also social significance and is of great importance in modern management systems.